Use of Hand Rehabilitation Board (Dominic’s Board) in Post Traumatic/Stroke Rehabilitation of the Upper Limbs - Essien, Dominic; Ekpenyong, Christopher (Journal of Sports Medicine and Therapy, 2017)
In recent years, the increasing number of patients with upper limb musculoskeletal disorders seeking timely, intensive, prolonged and task oriented hospital- and home- based physical rehabilitation, and the decreasing numbers of trained therapist to provide the needed care, have left a palpable gab. These have resulted in several preventable deformities with associated complications leading to social and economic burdens. Although the introduction of some robotic devices has addressed some of these concerns, the shortfalls from the use of these devices limit their effectiveness. The newly introduced hand rehabilitation board (Dominic’s Board) was prospectively evaluated in 82 patients with ULMDs of different etiologies to assess its therapeutic efficacy in rehabilitation of ULMDs. Additive, but complementary effect was observed when used along with conventional hospital-based therapy and at home, suggesting the effectiveness of this device in preventing or ameliorating the complications associated with ULMDs.